Quenching as a Route to Defect‐Rich Ru‐Pyrochlore Electrocatalysts toward the Oxygen Evolution Reaction. Issue 1 (25th November 2021) - Liu, Tongtong; Yang, Shaoxuan; Guan, Jingyu; Niu, Jin; Zhang, Zhengping; Wang, Feng
Abstract: Defects have a significant impact on the electrocatalysts performance. Introducing defect structures in metal oxides such as pyrochlores and perovskites has proved to be an effective strategy to enhance electrocatalytic activity. However, it is hard to build numerous defect sites in such high‐temperature oxides due to the strong metal–oxygen bonds and the so‐called self‐purification effect, which becomes increasingly important as the particle size reduced to the nanoscale. Here, a facile strategy is demonstrated to fabricate defect‐rich yttrium ruthenate oxides Y2 Ru2 O7− δ with the pyrochlore structure (denoted D rich ‐YRO) by the liquid nitrogen (<−196 °C) quenching. Owing to the almost instantaneous cooling in oxygen‐deficient condition, a large number of defects—including oxygen vacancies, grain boundaries, pores and surficial disorder—are preserved in the room temperature material and act as electrocatalytic active sites for oxygen evolution. As a result, D rich ‐YRO shows excellent catalytic activity and high electrochemical stability, along with a high performance in the operation of proton exchange membrane electrolyzer. The quenching strategy employed in this work provides a facile approach for constructing defect‐rich structures in high‐temperature oxides and should lead to new applications in energy conversion and storage devices for such materials. Abstract : The defect‐rich yttrium ruthenate oxides Y2 Ru2 O7− δ (denoted D rich ‐YRO) are fabricated by the liquid nitrogen (<−196 °C) quenching of Y2 Ru2 O7− δ produced by calcination at 1100 °C. Rich defects—including oxygen vacancies, grain boundaries, pores, and surficial disorder—resulting from the instantaneous cooling process, are preserved in room temperature material and act as electrocatalytic active sites for oxygen evolution.